Ariadne's thread in the age of artificial intelligence: : Parallels between the greek myth and WAME's recommendations (Colombia Medica, 2024)
Dear Editor,I am writing about the article titled “Chatbots, generative AI, and Scholarly Manuscripts: WAME Recommendations on Chatbots and Generative Artificial Intelligence about Scholarly Publications”. We aim to provide an additional perspective grounded in the well-known Greek myth of Daedalus Labyrinth and Ariadne’s Thread. In this ancient myth, it is told that Daedalus ingeniously created a baffling maze that served as a prison for the Minotaur, an exceptional being with both human and bull characteristics 2. Ariadne, madly in love with Theseus, kindly gifts him a subtle thread before his brave entrance into the labyrinth to confront the Minotaur. This thread becomes Theseus’s guide, ensuring he does not get lost in the confusion and disorder within the labyrinth’s complex corridors, and similarly provides him the tools to successfully find the route back to freedom after completing his dangerous mission.The ancient myth presented here can be interpreted as a metaphor that aids in understanding the “WAME recommendations” 1 in the context of artificial intelligence (AI) and its application in academic publications. The field of AI is acknowledged to be complex and accompanied by ethical and practical dilemmas, much like the labyrinth created by Daedalus. In this particular situation, the recommendations provided by WAME serve as our guiding thread, akin to Ariadne’s, helping us navigate through this complex environment.WAME’s first recommendation, which excludes “chatbots” as authors, underscores the importance of human responsibility and authorship in research. This can be likened to how Daedalus constructed the labyrinth but had no authority over what occurred within it. The second recommendation, advocating for transparency in the use of AI tools, can be compared to the thread that Theseus unravels, ensuring a transparent and verifiable research process. The other recommendations emphasize responsibility in content, the ethical use of AI by editors and reviewers, and the need for tools to detect AI-influenced content. These are fundamental in maintaining research integrity.